A missense mutation in the Hspa8 gene encoding heat shock cognate protein 70 causes neuroaxonal dystrophy in rats - Tanaka, Miyuu; Fujikawa, Ryoko; Sekiguchi, Takahiro; Hernandez, Jason; Johnson, Oleta T.; Tanaka, Daisuke; Kumafuji, Kenta; Serikawa, Tadao; Hoang Trung, Hieu; Hattori, Kosuke; Mashimo, Tomoji; Kuwamura, Mitsuru; et al. (Frontiers in Neuroscience, 2024)
Neuroaxonal dystrophy (NAD) is a neurodegenerative disease characterized by spheroid (swollen axon) formation in the nervous system. In the present study, we focused on a newly established autosomal recessive mutant strain of F344-kk/kk rats with hind limb gait abnormalities and ataxia from a young age. Histopathologically, a number of axonal spheroids were observed throughout the central nervous system, including the spinal cord (mainly in the dorsal cord), brain stem, and cerebellum in F344-kk/kk rats. Transmission electron microscopic observation of the spinal cord revealed accumulation of electron-dense bodies, degenerated abnormal mitochondria, as well as membranous or tubular structures in the axonal spheroids. Based on these neuropathological findings, F344-kk/kk rats were diagnosed with NAD. By a positional cloning approach, we identified a missense mutation (V95E) in the Hspa8 (heat shock protein family A (Hsp70) member 8) gene located on chromosome 8 of the F344-kk/kk rat genome. Furthermore, we developed the Hspa8 knock-in (KI) rats with the V95E mutation using the CRISPR-Cas system. Homozygous Hspa8-KI rats exhibited ataxia and axonal spheroids similar to those of F344-kk/kk rats. The V95E mutant HSC70 protein exhibited the significant but modest decrease in the maximum hydrolysis rate of ATPase when stimulated by co-chaperons DnaJB4 and BAG1 in vitro, which suggests the functional deficit in the V95E HSC70. Together, our findings provide the first evidence that the genetic alteration of the Hspa8 gene caused NAD in mammals.